Transposable Elements in the Organization and Diversification of the Genome of Aegilops speltoides Tausch (Poaceae, Triticeae) - Olga Raskina (International Journal of Genomics)
Repetitive DNA—specifically, transposable elements (TEs)—is a prevailing genomic fraction in cereals that underlies extensive genome reshuffling and intraspecific diversification in the wild. Although large amounts of data have been accumulated, the effect of TEs on the genome architecture and functioning is not fully understood. Here, plant genome organization was addressed by means of cloning and sequencing TE fragments of different types, which compose the largest portion of the Aegilops speltoides genome. Individual genotypes were analyzed cytogenetically using the cloned TE fragments as the DNA probes for fluorescence in situ hybridization (FISH). The obtained TE sequences of the Ty1-copia, Ty3-gypsy, LINE, and CACTA superfamilies showed the relatedness of the Ae. speltoides genome to the Triticeae tribe and similarities to evolutionarily distant species. A significant number of clones consisted of intercalated fragments of TEs of various types, in which Fatima (Ty3-gypsy) sequences predominated. At the chromosomal level, different TE clones demonstrated sequence-specific patterning, emphasizing the effect of the TE fraction on the Ae. speltoides genome architecture and intraspecific diversification. Altogether, the obtained data highlight the current species-specific organization and patterning of the mobile element fraction and point to ancient evolutionary events in the genome of Ae. speltoides.